HUBUNGAN ANTARA PERILAKU CARING PERAWAT DENGAN SRATEGI KOPING KELUARGA (PRIMARY CAREGIVER) YANG ANGGOTA KELUARGANYA DIRAWAT DI INSTALASI GAWAT DARURAT - Muhamad Irfanudin; Achir Yani S. Hamid; Titin Ungsianik (Jurnal Kesehatan, 2020)
Background: Caring behavior of nurses is the essence of nursing science ("the heart of nursing"), as this is what determines the quality and service quality nursing care and will directly affect coping strategies family (primary caregiver) who had family members get care in the emergency department (ED). This study aims to identify the correlation between nurse caring behaviors with family coping strategies (caregiver) whose family members were treated in the ED. Methods: This study used a descriptive correlation approach, with a total sample of 75 respondents, the sample selection was conducted by sampling proposive. The research instrument used Assesmant Caring Behavior Tool (CBA) and F Copes (Family Crisis Oriented Personal Scales). Results: of the study found that there is no correlation between nurse caring behaviors with family coping strategies whose family members were treated in emergency care with a value of P 0.938 and r -0.009 Conclusion: of this study imply that nurses caring behavior should be used as a culture in providing nursing care and hospital management determines the policies related policies on caring behavior of nurses in emergency department service